Al-Qarḍ al-Ḥasan Program of Bankziska: Zakat Fund-Based Empowerment Model for Victims of Loan Sharks - Iza Hanifuddin; Nur Kasanah; Eficandra Eficandra (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This research aimed at analyzing the effectiveness of the Bankziska program in empowering victims of loan sharks through the al-Qarḍ al-Ḥasan contract funded by zakat, administered by the Amil Zakat Infaq and Shadaqah of Muhammadiyah Institutions. Qualitative method was used in this research with a phenomenological approach using the activity data from the Amil Zakat Infaq and Shadaqah of Muhammadiyah Institutions in empowering loan shark victims through the Bankziska program. The data sources were obtained from managers, volunteers, and loan shark victims who were the partners of Bankziska. The research results showed that the reasons for the Amil Zakat Infaq and Shadaqah of Muhammadiyah Institutions to lend zakat funds were the references from fiqh and fatwa, training studies, organizational encouragement, academic input, and it is easy to implement. The implementation of the Bankziska program had detailed standard operating procedures, starting from the beneficiary categories, distribution, and payment processes, to mitigating the risk of default. The al-Qarḍ al-Ḥasan program of Bankziska had an impact on improving the quality of skills, mental, intellectual, technological, communication, and religious studies of managers and volunteers. The impact of the program for partners was the awareness to abandon usury, reduced debt both in nominal terms and the number of loan sharks and an increase in the ethos of economic independence. This research contributes to providing discourse and alternatives for other social and religious fund management institutions in using zakat funds productively for economic empowerment through the al-Qarḍ al-Ḥasan contract for victims of loan sharks who have difficulty accessing Sharia financial institutions to obtain business capital or financing services.